LANDSCAPE-BIOTOPICAL VARIABILITY OF EGGS OF YELLOW-LEGGED GULL IN STAVROPOL REGION - Mikhail P. Ilyukh (Вестник Северо-Кавказского федерального университета)
The article describes the analysis of landscape-biotopical variability of eggs of the very numerous and distributions gull in Stavropol region - yellow-legged gull Larus cachinnans - reveal reliable difference oo- morphometrical parameters in diverse geographical conditions, that evidence on territorial heterogeneous and separate of population given species gull in region.